Liver transplantation in gastroenteropancreatic neuroendocrine tumors - Fernandes, Eduardo de Souza M.; Kyt, Camila V. Garcia; de Mello, Felipe Pedreira Tavares; Pimentel, Leandro Savattone; Andrade, Ronaldo de Oliveira; Girão, Camila; César, Camilla; Siqueira, Munique; Monachesi, Maria Eduarda; Brito, Anderson; Tavares de Sousa, Claudia Cristina; Andraus, Wellington; et al. (Frontiers in Oncology, 2023)
Neuroendocrine tumors are part of a heterogeneous group of tumors located in organs such as the gastrointestinal tract (GIT), lungs, thymus, thyroid, and adrenal glands. The most prevalent sites are the small intestine, cecal appendix, and pancreas. More than 50% of these tumors are associated with metastases at the time of diagnosis. Neuroendocrine tumors are classified according to the degree of cell differentiation and the histopathological proliferation index of the lesion. Neuroendocrine tumors can be well differentiated or poorly differentiated. G3 tumors are characterized by Ki-67 expression greater than 20% and can be either well differentiated (G3 NET) or poorly differentiated (G3 NEC). Neuroendocrine carcinoma (NEC G3) is subdivided into small-cell and large-cell types. When neuroendocrine tumors present clinical and compressive symptoms, carcinoid syndrome is evident. Carcinoid syndrome occurs when the tumor produces neuroendocrine mediators that cannot be metabolized by the liver due to either the size of the tumor or their secretion by the liver itself. Several therapeutic strategies have been described for the treatment of metastatic neuroendocrine tumors, including curative or palliative surgical approaches, peptide receptor radionuclide therapy, percutaneous therapy, systemic chemotherapy, and radiotherapy. Liver surgery is the only approach that can offer a cure for metastatic patients. Liver metastases must be completely resected, and in this context, orthotopic liver transplantation has gained prominence for yielding very promising outcomes in selected cases. The aim of this study is to review the literature on OLT as a form of treatment with curative intent for patients with gastroenteropancreatic neuroendocrine tumors with liver metastasis.